Flexible Batteries: Flexible Na/K‐Ion Full Batteries from the Renewable Cotton Cloth–Derived Stable, Low‐Cost, and Binder‐Free Anode and Cathode (Adv. Energy Mater. 38/2019). Issue 38 (10th October 2019) - Guo, Jin‐Zhi; Gu, Zhen‐Yi; Zhao, Xin‐Xin; Wang, Mei‐Yi; Yang, Xu; Yang, Yang; Li, Wen‐Hao; Wu, Xing‐Long
Abstract : In article number1902056, Xing‐Long Wu, and co‐workers put forward an advanced strategy to simultaneously prepare flexible anodes and cathodes by utilizing commercially available cotton cloth as a precursor, and then design the corresponding flexible Na/K‐ion batteries, which exhibit promising energy‐storage performance and remarkable flexibility.